Analysis of office supply management and disbursement system to enhance efficiency at PT API - Pramalegawa, I Kadek Ary; Kasiani, Kasiani; Kencanawati, A.A. Ayu Mirah (Journal of Commerce, Management, and Tourism Studies, 2025)
The management of office stationery supplies (ATK) plays a crucial role in supporting the operational efficiency of a company, especially in daily administrative activities. This study aims to analyse the method of disbursement and determination of stationery inventory at PT API. A qualitative approach with a case study method was employed. Data collection techniques included interviews, direct observations, and documentation of goods receipt and disbursement reports in the company's asset unit. The analysis reveals that the ATK disbursement method currently in use is still periodic and not entirely based on actual data, resulting in discrepancies between stock levels and real operational needs. Additionally, the determination of inventory levels is conducted without the implementation of a standardized system, which poses risks of both overstocking and stock shortages. The application of the FIFO (First In, First Out) method is considered more appropriate in this context as it improves inventory management efficiency, reduces waste, and reflects a more realistic inventory value in financial reporting. The study concludes that the implementation of a data-based inventory management system and standardized Standard Operating Procedures (SOPs) is essential to ensure better control over ATK disbursement and to support corporate accountability. This would also align inventory practices with operational demands and financial transparency.